Joseph Skoda - N. A. Makatsariya; I. V. Khamani; D. A. Doronicheva (Акушерство, гинекология и репродукция, 2023)
Here, we describe the historical aspects of the life and scientific work of Joseph Skoda as well as his contribution to medicine.